Cooperative Script Method For Student’s Islamic Economic Law on English Learning - Amrizal Amrizal; Zohri Hamdani; Winda Putri Ardina (ILIN Institute Makassar, 2020)
This study is going to know what cooperative script method can increase students’ English skill on Islamic economic law especially in past tense material. This study used class action research and the data of collecting used pre test and post test. The population in this study was 60 students in first semester, Students’ Islamic economic law, State College of Islamic studies (STAIN) Mandailing Natal and used random sampling technique as sample, there were 30 students as sample. The analysis data used average score. The result of this study shows that cooperative give good significant in learning English especially in past tense material in first semester, Students’ Islamic economic law, State College of Islamic studies (STAIN) Mandailing Natal